Zakat and Waqf as an Islamic Microfinance Tool to Uplift Social and Economic Life of the People in Tajikistan - Mirzoev, Sharofiddin (International Journal of Islamic Economics and Governance, 2025)
Zakat and waqf as an Islamic tool for Islamic microfinance has become increasingly relevant. Both these practices were historically institutionalized in Muslim communities since the rule of the Prophet (PBUH) himself. These practices develop a culture of shared equality within the community, eventually improving social ties and cohesion as well. The benefit of zakat and waqf as an Islamic microfinance tool is that it not only generates funds for the poor, but also creates sustainable solutions by creating sources of employment and education that effectively treats the problem of poverty. Tajikistan is one of the Muslim countries which is suffering from poverty and huge income gap between poor and rich. It is imperative to bring into consideration the development of constructive policies like zakat and waqf being an Islamic microfinance tool that will not only mitigate the country’s vulnerabilities to external factors but also contribute in the economic growth and development of the country. The paper not only explores the effectiveness of zakat and waqf as an Islamic microfinance tool but also assesses its relevance in the context of Tajikistan in uplifting the social and economic life of the people in the country. This implies that Tajikistan is yet to come up with a tool for poverty alleviation that is safeguarded from these external economic and social factors. The paper will also provide recommendations regarding policy adaptation and how the funds can be utilized for upliftment of poor through multichannel programs. © 2025 The Author(s). Licensed under CC BY-NC 4.0.